Promising fuels for energetics: Spherical Al-Li powders with high reactivity via incorporation of Li. (1st September 2022) - Zhu, Yanli; Le, Wei; Zhao, Wanjun; Ma, Xiaohang; Liu, Dazhi; Li, Jianxin; Jiao, Qingjie
Highlights: Spherical Al-Li alloys were originally prepared via the centrifugal atomization. Prepared Al-Li alloys consist of evenly-distributed α-Al and Al-Li compounds. Al-Li alloys show higher heat release and reaction rate than pure Al. The shorter ignition delay of Al-Li/KP than Al/KP is due to lower Ea of Al-Li. Microexplosion has been observed when Al-Li alloys are used in energetic materials. Abstract: To improve the heat release and reactivity of Al, Li was incorporated into Al via the centrifugal atomization in this study for obtaining Al-Li alloy powders. The microstructure and composition of the samples were characterized by SEM, XRD, and ICP. The oxidation kinetics were evaluated via TG/DSC, and the energetic performance of the Al-Li/KP composites was tested. The results show that spherical Al-Li alloy powders with the well-distributed dendritic structure are obtained that are mainly composed of αAl and Al-Li compounds. The oxidization rate of Al-Li alloy powders is higher than pure Al, owing to the decreasing activation energy caused by the catalysis of the soluble Li in Al and Al-Li compounds. The shorter ignition delay and higher reaction rate of Al-Li/KP with increasing Li content in Al-Li alloy powders is a result of the microexplosion of Al-Li. Therefore, Al-Li alloy powders with high reactivity are promising fuels for energetic materials.